Epidemiology of community-acquired pneumonia among hospitalised children in Indonesia: a multicentre, prospective study. Issue 6 (21st June 2022) - Lokida, Dewi; Farida, Helmia; Triasih, Rina; Mardian, Yan; Kosasih, Herman; Naysilla, Adhella Menur; Budiman, Arif; Hayuningsih, Chakrawati; Anam, Moh Syarofil; Wastoro, Dwi; Mujahidah, Mujahidah; Dipayana, Setya; et al.
Abstract : Objective: To identify aetiologies of childhood community-acquired pneumonia (CAP) based on a comprehensive diagnostic approach. Design: 'Partnerships for Enhanced Engagement in Research-Pneumonia in Paediatrics (PEER-PePPeS)' study was an observational prospective cohort study conducted from July 2017 to September 2019. Setting: Government referral teaching hospitals and satellite sites in three cities in Indonesia: Semarang, Yogyakarta and Tangerang. Participants: Hospitalised children aged 2–59 months who met the criteria for pneumonia were eligible. Children were excluded if they had been hospitalised for >24 hours; had malignancy or history of malignancy; a history of long-term (>2 months) steroid therapy, or conditions that might interfere with compliance with study procedures. Main outcome(s) measure(s): Causative bacterial, viral or mixed pathogen(s) for pneumonia were determined using microbiological, molecular and serological tests from routinely collected specimens (blood, sputum and nasopharyngeal swabs). We applied a previously published algorithm (PEER-PePPeS rules) to determine the causative pathogen(s). Results: 188 subjects were enrolled. Based on our algorithm, 48 (25.5%) had a bacterial infection, 31 (16.5%) had a viral infection, 76 (40.4%) had mixed bacterial and viral infections, and 33 (17.6%) were unable to be classified. The five most common causative pathogens identified were Haemophilus influenzae non-type B (N=73, 38.8%), respiratory syncytial virus (RSV) (N=51, 27.1%), Klebsiella pneumoniae (N=43, 22.9%), Streptococcus pneumoniae (N=29, 15.4%) and Influenza virus (N=25, 13.3%). RSV and influenza virus diagnoses were highly associated with Indonesia's rainy season (November–March). The PCR assays on induced sputum (IS) specimens captured most of the pathogens identified in this study. Conclusions: Our study found that H. influenzae non-type B and RSV were the most frequently identified pathogens causing hospitalised CAP among Indonesian children aged 2–59 months old. Our study also highlights the importance of PCR for diagnosis and by extension, appropriate use of antimicrobials. Trail registration number: NCT03366454